A Critical Analysis the Impact of Midwifery and Nursing Assistants on Reducing Maternal Mortality Rates Hospitals - ALGASHAINEN, SAEED MOHAMMED SALEH; ALRUBUA, SALEH MAHDI ABDULLAH; AL-SHAHRANI, BUDOUR NASSER FAYEZ; AL-SHAHRANI, NOURA BADIE HAIDER; AL SHAMRANI, HANADI KHABZAN; BALHARITH, TAGHREED SALEH HADI; LASLOOM, FARID JABER HADI; AL HARITH, SALEM SALEH MESFER; AL MUSTANEER, MONA ALI GHALEB; ALMONABEHI, NOUF ALI MOHAMMAD (Journal of Ecohumanism, 2024)
According to the data analyzed, healthcare has recently recorded increased improvement concerning using health assistants to supplement the nursing workers and aid the patients. Qualified or employed to undertake various clerical, technical, and patient care roles, health assistants are steadily incorporated into the nursing team to enhance productivity and effectiveness in presenting quality services to patients. The purpose of this study is to critique the existing literature regarding the effects of health assistants on the productivity of nurses and the quality of patient care. Conducting a literature review, observational study, and analysis of data from health facilities, the study offers a new understanding of how health assistants may contribute to minimizing nurse workload, enhancing patient care status, and supporting the functioning of health systems. The outcomes indicate that health assistants positively impact the efficiency of the nurses they support; however, practical issues should be resolved to enhance the effect: role definition and standardized training.